Pengaruh Komunikasi Interpersonal Pelayanan External Debt Collector terhadap Tingkat Kepuasan Nasabah PT. Clipan Finance Indonesia Cabang Surabaya - Reno Yudha Prasetya Arifin; Nevrettia Christantyawati (Jurnal Komunikasi Global, 2017)
This research examines the effect of interpersonal communication of external debt collector service to customer satisfaction level at PT. Clipan Finance Indonesia Surabaya Branch. The research used a simple correlational method in which the variable x is interpersonal communication external debt collector service and variable y is level of customers’ satisfaction. Researchers use survey by distributing questionnaire as data collecting technique. In the processing stage, researchers used editing, coding and tabulating. The data analysis technique used correlation analysis and simple linear regression analysis. The results showed that there was insignificant influence between interpersonal communication variables external debt collector service to the level of customer satisfaction of bad credit at PT. Clipan Finance Indonesia Surabaya Branch.